STUDY ON THE NEOPRENE DEGRADATION UNDER COMBINATION EFFECT OF OVEN AGEING AND FATIGUE (Sciences & Technologie. B, Sciences de l'ingénieur, 2008)
The forecasting of the neoprene lifetime constitutes a major industrial stake for the set of the mechanical manufactured elements with this material like the flexible shaft and automotive belts. The use of this material in these cases, besides, shown that this material deteriorated again more quickly under the combination effect of temperature and fatigue. To characterize this, we carried fatigue tests in alternate tension on a set of new neoprene specimens and ageing ones during 48h and 96h at 100°C into a universal ventilated steam room. The experimental results show, that the (S,N) curves for the three sets of specimens have the same shape and that the fatigue strength brutally falls between the new sample and the aged ones, indicating a loss of fatigue characteristics of this material under accelerated ageing.